Evaluation of Cervical Myoclonus in Dogs with Spinal Diseases: 113 Cases (2014–2023) - Ana Martinez; Emili Alcoverro; Edward Ives; Lisa Alves (Animals)
Cervical myoclonus (CM) has been associated with intervertebral disc extrusion (IVDE), with a higher prevalence in French Bulldogs. The presence of CM in other breeds and with other aetiologies has not been reported. The purpose of this study was to describe the signalment, neurological examination, neuroanatomical localisation and grade, imaging findings, diagnosis, treatment, follow-up and resolution of CM in dogs. An observational multicentred retrospective analysis identified 173 dogs with CM; of those, 113 met the inclusion criteria. French Bulldogs (n = 52/113, 46%), Beagles (n = 8/113, 7.1%), Chihuahuas and Shih-Tzus (n = 6/113 for each, 5.31%) were the most affected breeds. Apparent cervical pain was the most common finding on neurologic examination (n = 70/113, 62%). Magnetic resonance imaging (MRI) was consistent with nerve root impingement in 17% (n = 19/113) of the dogs. The most frequently diagnosed conditions were degenerative (n = 100/113, 88.5%), inflammatory (n = 8/113, 7.1%), neoplastic (n = 3/113, 2.7%), vascular (n = 1/113, 0.9%) and congenital (n = 1/113, 0.9%) in origin. Dogs with a neoplastic aetiology tended to be older than those with other causes. Follow-up was recorded in 77 dogs, and 75 of these (n = 75/77, 97.4%) had resolution of the CM. The results supported that cervical myoclonus can be caused by various underlying conditions and can affect different dog breeds.